1952
DOI: 10.1021/ac60063a011
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Chemistry of Niobium and Tantalum. Critical Analysis of Existing Methods

Abstract: Table VI. Silicon Determination in Calcium Oxide" with and without Fluoride Treatment (7 silicon per 100 ml.) With Without Fluoride & Fluoride 137 98 138 96 136 96 136 91 137 95" A 1-gram sample was dissolved in dilute hydrochloric acid, transferred 100-ml. volumetric flask, and made to volume. Solution was filtered and 2-ml. aliquots were removed for analysis.b The 2-ml. aliquots were diluted with water, treated with 0.5 ml. of zirconium-fluoride solution, and warmed for 0.5 hour.The effect oí fluoride treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1952
1952
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Here the difference between nickel and the refractory metals is obvious: Nickel can bind to only two chlorine atoms at most . The refractory metals on the other hand need to form much higher coordinated compounds, up to hepta‐ (NbCl 5 , TaCl 5 , MoCl 5 , WCl 5 ) and hexachlorides (WCl 6 ), in order to become stable enough to disengage from the surface .…”
Section: Reaction Mechanisms Of the High Temperature Chlorination Of mentioning
confidence: 99%
“…Here the difference between nickel and the refractory metals is obvious: Nickel can bind to only two chlorine atoms at most . The refractory metals on the other hand need to form much higher coordinated compounds, up to hepta‐ (NbCl 5 , TaCl 5 , MoCl 5 , WCl 5 ) and hexachlorides (WCl 6 ), in order to become stable enough to disengage from the surface .…”
Section: Reaction Mechanisms Of the High Temperature Chlorination Of mentioning
confidence: 99%
“…This process involves the chlorination of titanium-rich ore to form TiC14. Since TiC14 boils at 136°C and NbC15 at 243°C, conditions are favorable for obtaining good separations, as recently demonstrated Atkinson, Steigman, and Hiskey (1952). Further research on the process is obviously needed, as well as a study of the economic factors.…”
Section: Possibility Of Recovery Of Niobium From Arkansas Bauxite Andmentioning
confidence: 97%
“…Berry et al (1) used sucrose as an example of a compound which caused large errors because of viscosity. Bills et al (2) showed that the presence of 5000 p.p.m. of glycerol with 5 p.p.m.…”
Section: Discussionmentioning
confidence: 99%